FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN IMUNISASI DASAR PADA BAYI DI WILAYAH KERJA PUSKESMAS BOTANIA - Kristin, Welsi Yunira; Mona, Silvia (Universitas Batam, 2019)
Immunization is a process to make the body's defense system immune to invasion of microorganisms; Puskesmas Botania is the lowest complete basic immunization coverage of 80.5% of the 14 Puskesmas in Batam. The purpose of the study was to determine the factors that influence the infants’ completeness of basic immunization at Puskesmas Botania work area in 2018. The study was conducted on May 4 to July 17 2018 with 96 respondents, purposive sampling and cross sectional design. The data was collected by primary and secondary using questionnaires, KIA and KMS. Univariate and Bivariate analysis applied chi-square. The conclusion of basic majority education (54 people), employment status work (54 people), supportive family support (60 people) and the majority of incomplete immunizations (56 respondents) and there are relationships of all factors studied such as education, employment status and family support for completeness of basic immunization with (p-value 0.000). It is suggested for Puskesmas to provide counseling for parents, especially the infant's father about the importance of immunization.